Does Apical Papilla Survive and Develop in Apical Periodontitis Presence after Regenerative Endodontic Procedures? - Paulo J. Palma (Applied Sciences, 2019)
Regenerative endodontic procedures (REPs) have emerged as a treatment option for immature necrotic teeth to allow the reestablishment of a newly formed vital tissue and enable continued root development. The apical papilla stem cells (SCAPs) play an important role in physiologic root development and may also contribute to further root development during REPs. The goal of these case reports is to show evidence of the apical papilla survival and development, in human teeth with apical periodontitis, after REPs, with 5-year clinical and radiographic follow-up. In the first case, an 11-year-old girl with acute apical abscess of tooth 15 was referred for a REP. Treatment was performed with an intracanal medication followed by induction of a blood clot and a Mineral Trioxide Aggregate (MTA) cervical barrier. The 5-year follow-up showed an appreciable increase in root length as well as root canal thickness. In case 2, a 16-year-old girl was referred for endodontic treatment of tooth 21. The parents of the patient recalled a previous dental trauma (no specified on the patient records) on tooth 21 at age 7. The dental history reports a previous endodontic treatment failure and presence of a long-standing sinus tract. A mineralized tissue beyond the root apical portion could be seen at the preoperative X-ray. Nonsurgical root canal retreatment with an apical barrier was suggested as the treatment plan and accepted by the patient. After 2 weeks, the patient was recalled for a follow-up appointment presenting spontaneous pain, swelling, and sinus tract. Apical surgery was performed. Histopathological assessment of the apical root fragment collected showed the presence of dentin, cementum and pulp tissue, including odontoblasts. The 5-year follow-up depicted complete apical healing. The present case reports support survival and continued potential differentiation of the apical papilla after endodontic infection.